Effect of holding time during hot compression moulding on mechanical performance of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) - Mustafa, Zaleha; Chang, Siang Yee; Mohammad Sappa, Amirah Ain Asyiqin; Sheikh Md Fadzullah, Siti Hajar; Ahsan, Qumrul (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) is a biopolymer known for its biodegradable and non-toxic properties. In this study, the PHVB was subjected to various holding times to investigate the influence of thermal exposure on the mechanical performance, crystallinity and morphology of the PHBV. The compression pressure of 25 000 psi at the optimum temperature of 175 °C was used while the holding time was set to 18, 23 and 28 minutes. The results indicate that holding time influences the formation of pores, uniformity of polymer melting, crystallinity, and tensile and flexural properties of the PHVB. The highest tensile strength (22.01 MPa) and Young's modulus (4.9 GPa) and flexural strength and modulus at 70.82 MPa and 21.6 GPa, respectively were obtained when 23 minutes of holding time were used. Morphological analysis through SEM shows the presence of pores and crack propagation, emphasising the impact of holding time on plastic deformation. The study concludes that selecting appropriate processing conditions is crucial for optimising the performance of PHBV, addressing challenges associated with its narrow processing window.